1990
DOI: 10.1111/j.1365-2044.1990.tb14689.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory obstruction after posterior fossa surgery

Abstract: SummaryWe report a case, of acute upper airway obstruction after tracheal extubation 24 hours after surgery. The respiratory complications of surgery for posterior fossa lesions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…9 In addition, if there is any doubt about the integrity of bulbar function, the endotracheal tube should be kept in place for 24 h after surgery. 17 The high rate of delayed extubation in the present study suggests that the decision-making process in the authors' study centre may be over-conservative. It should be noted that 69.9% of patients included in the present report had tumours !30 mm in diameter, which is a higher rate than the 54% incidence reported elsewhere.…”
Section: Discussionmentioning
confidence: 77%
“…9 In addition, if there is any doubt about the integrity of bulbar function, the endotracheal tube should be kept in place for 24 h after surgery. 17 The high rate of delayed extubation in the present study suggests that the decision-making process in the authors' study centre may be over-conservative. It should be noted that 69.9% of patients included in the present report had tumours !30 mm in diameter, which is a higher rate than the 54% incidence reported elsewhere.…”
Section: Discussionmentioning
confidence: 77%
“…[6] Patients undergoing posterior fossa surgery are at an even higher risk of developing POPCs because of the interplay of other mechanisms like mechanical obstruction, central respiratory dysfunction, and neuromuscular dysfunction. [7] Obstructive sleep apnea has been reported in association with posterior fossa lesions. [8] The risk factors for POPCs in this group of patients have not been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…214 Howard and colleagues described a patient with a recurrent choroid plexus papilloma involving the fourth ventricle. 215 Preoperatively, the patient displayed bulbar dysfunction. His extubation on the first postoperative day was complicated by complete airway obstruction, hypoxia, and a seizure.…”
Section: Posterior Fossa Surgerymentioning
confidence: 98%
“…Posterior fossa surgery can cause injury to cranial nerves, bilateral vocal cord paralysis, brainstem or respiratory control center injury, and macroglossia. 114,115,167,[213][214][215][216] Because the nerve roots may be very close to the operative site, the resultant injuries may be bilateral, extensive, and transient or permanent. Gorski and coworkers suggested that tolerance of the ETT and the absence of a gag reflex on oral suctioning should arouse suspicion of such an injury.…”
Section: Posterior Fossa Surgerymentioning
confidence: 99%